2017
DOI: 10.1007/s12975-017-0576-9
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Deformations and Entorhinal Cortex Atrophy as an Anatomical Signature of Long-Term Cognitive Impairment: from the MCAO Rat Model to the Stroke Patient

Abstract: Stroke patients have an elevated risk of developing long-term cognitive disorders or dementia. The latter is often associated with atrophy of the medial temporal lobe. However, it is not clear whether hippocampal and entorhinal cortex atrophy is the sole predictor of long-term post-stroke dementia. We hypothesized that hippocampal deformation (rather than atrophy) is a predictive marker of long-term post-stroke dementia on a rat model and tested this hypothesis in a prospective cohort of stroke patients.Male W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…As known, the hippocampus plays an important role in memory formation [39] , Floro-Jade C staining was used to see whether AVE can attenuate neuronal degeneration in different regions of ipsilateral hippocampus. Robust Floro-Jade C staining in CA1, CA2, and DG of ipsilateral hippocampus were observed at 28 d after SAH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As known, the hippocampus plays an important role in memory formation [39] , Floro-Jade C staining was used to see whether AVE can attenuate neuronal degeneration in different regions of ipsilateral hippocampus. Robust Floro-Jade C staining in CA1, CA2, and DG of ipsilateral hippocampus were observed at 28 d after SAH.…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampus injury in animal models of ischemia has been shown to cause long-term cognitive impairments [39] , [54] . Interestingly, our study showed that neurodegenerations of CA1, CA2, and DG of the hippocampus were evident even 28 d after SAH as measured in Fluoro-Jade C staining.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting imbalance in vasodilation, neuroinflammation, oxidative stress, and thrombogenesis could contribute to stroke pathophysiology during SARS-CoV-2 infection. 50 Our results indicated a broad presence of ACE2 and TMPRSS2 in CNS tissues that are closely associated with stroke, including the cerebellum, 51 corpus callosum, 52 hippocampus, 53 frontal lobe, 54 cerebral cortex, 55 and others. Therefore, the tissue tropism of SARS-CoV-2 for ACE2 (or TMPRSS2) and the inflammatory cytokine storm caused by COVID-19 might be an underlying mechanism for stroke.…”
Section: Discussionmentioning
confidence: 72%
“…Through a translational approach using data from both an animal model and patients with minor stroke, we found that hippocampal deformations and entorhinal cortex atrophy would be an anatomic signature of long-term cognitive impairment. 7 In male wistar rats subjected to transient middle cerebral artery occlusion, significant impairments in hippocampus-dependent memories were observed 6 months later without significant atrophy of the hippocampus volume but with a significant deformation and thinner entorhinal cortex in magnetic resonance imaging studies. In parallel, in 90 initially dementia-free patients having experienced a first-ever minor stroke, more than half displayed cognitive impairments at 6-month poststroke with a decrease in both Montreal Cognitive Assessment and Mini-Mental State Examination.…”
Section: See Related Article P 384mentioning
confidence: 99%
“…Shape analysis revealed marked deformations of their left hippocampus and a significantly lower entorhinal cortex surface without any hippocampal atrophy. 7 Similarly, changes in hippocampal mean diffusivity and hippocampal connectivity predict cognitive state at 6 and 12 months after a mild stroke. 8 Structural and functional changes, including these subtle changes to hippocampal shape and texture, atrophy in areas outside of hippocampus, and disruption to functional networks are also seen in the course of Alzheimer disease, 9 suggesting that TIA or minor stroke possibly induce a long-term neurodegenerative process.…”
Section: See Related Article P 384mentioning
confidence: 99%